The trade margins of Chinese agricultural exports to ASEAN and their determinants - Zhi-lu SUN; Xian-de LI (Journal of Integrative Agriculture, 2018)
How do Chinese agricultural exports to ASEAN (Association of Southeast Asian Nations) evolve? And what factors affected the evolution pattern? This study measures the trade margins of Chinese agricultural exports to ASEAN by utilizing the 2000–2015 Harmonized System's six-digit agricultural trade data, and further analyzes their determinants by developing an augmented gravity model of international trade. The results indicate that, the main growth source of Chinese agricultural exports to ASEAN has shifted from the extensive margin before the formal establishment of CAFTA (China–ASEAN Free Trade Area) in 2010 to the intensive margin since the formal establishment of CAFTA, but changes in Chinese agricultural exports to ASEAN have always mainly depended on the intensive margin. Since the formal establishment of CAFTA, the evolution pattern of Chinese agricultural exports to ASEAN has shifted from “more varieties, low price, and small quantity” to “less varieties, high price, and large quantity”. Relative economic scale, relative population scale, capacity of agricultural export, trade integration, global financial crisis, and common border significantly affect the trade margins of Chinese agricultural exports to ASEAN.